Do attacks by jaguars Panthera onca and pumas Puma concolor (Carnivora: Felidae) on livestock correlate with species richness and relative abundance of wild prey? - Burgas, Albert; Amit, Ronit; Lopez, Bernat C. (Revista de Biología Tropical, 2014)
Attacks by big cats on livestock are one of the major causes of human-felid conflicts and, therefore, an important factor in the conservation of these species. It has been argued that a reduction in natural prey abundance promotes attacks on domestic species, but few studies have tested this statement, and some have delivered contradictory results. We investigated whether the occurrence of attacks to livestock by jaguar and puma relates to the abundance and richness of their natural prey. In the rainy season 2009, we tracked potential prey species counting signs of presence along linear transects in 14 non-attacked cattle farms (control) and in 14 attacked cattle farms in NW Costa Rica. There was a negative relationship between the occurrence of attacks and both species richness (p=0.0014) and abundance (p=0.0012) of natural prey. Our results support the establishment of actions to promote support and recovery of natural prey, in order to diminish attacks on livestock, while maintaining jaguar and puma populations. awareness of the educational cervical cancer campaign (7.7% of the student population) and the ability to go alone to the doctor to receive medical attention (30.6% of students). Additionally, the public education system does not require cervical cancer to be included in the present curriculum. Hence, as students lack education on prevention and risk factors, the majority of prevention responsibility falls only on the universal health care system to regularly perform Papanicolaou exams to detect pre-cancerous or cancerous changes. The findings indicated the importance of including cervical cancer in the sexual education curriculum of the public education system in Costa Rica to educate the at-risk population of preventative methods, infection development, clinical manifestations and medical services in order to lower the presence of cervical cancer. Albert Burgas 1, Ronit Amit 2* & Bernat C. Lopez3 1 Unit of Ecology, Autonomous University of Barcelona, CREAF, Edifici C, 08193 Cerdanyola del Vallès, Catalunya, Spain; aburgas@gmail.com 2 Department of Wildlife Ecology and Conservation, University of Florida, 110 Newins-Ziegler Hall, PO Box 110430, Gainesville, FL 32611-0430, USA; jaguar.rar@gmail.com 3 Unit of Ecology, Autonomous University of Barcelona, CREAF, Edifici C, 08193 Cerdanyola del Vallès, Catalunya, Spain; bernat.claramunt@uab.cat